Design and Preparation of Zaltoprofen-Nicotinamide Pharmaceutical Cocrystals via Liquid Assisted Grinding Method - Panzade, Prabhakar; Shendarkar, Giridhar (Indian Journal of Pharmaceutical Education and Research, 2019)
Introduction: Pharmaceutical cocrystal is an endowed approach to augment solubility and dissolution of drugs with limited aqueous solubility. Zaltoprofen is a nonsteroidal anti-inflammatory drug with prevailing solubility problem. The present study deciphers preparation of cocrystals of lipophilic drug zaltoprofen to improve the solubility and dissolution by screening various coformers. Methods: Cocrystals of zaltoprofen were prepared in 1:1 and 1:2 molar ratio of drug: coformer by liquid assisted grinding method. The crystalline phase was subjected to evaluation by melting point and solubility. The potential cocrystals were characterized by differential scanning calorimetry (DSC), infrared spectroscopy (IR), powder X-ray diffraction (PXRD) and scanning electron microscopy (SEM). Dissolution rate and stability of cocrystals was also investigated. Results: Zaltoprofen-nicotinamide (ZFN-nicotinamide) cocrystals revealed variation in melting point and solubility. Two cocrystals were obtained in 1:1 and 1:2 ratios with nicotinamide. IR spectrum distinctly showed the shifting of typical absorption bands of zaltoprofen. Crystallinity of cocrystals was clear from the PXRD pattern and noteworthy difference in 2θ value of intense peaks. DSC spectra of cocrystals revealed altered endotherms analogous to melting point. Cocrystals exhibited rapid dissolution rate and 56% increase in the extent of dissolution compared to pure drug. The cocrystals were found stable at stability conditions. SEM revealed difference in the crystal morphology. Conclusion: Hence, it can be concluded that ZFN-nicotinamide cocrystal could present an improved drug design approach to surmount dissolution and bioavailability related challenges linked with lipophilic drug zaltoprofen.
Keywords: Cocrystal; Zaltoprofen; Liquid assisted grinding; Solubility; Dissolution